PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DESA DI DESA KERASWETAN KECAMATAN GENENG KABUPATEN NGAWI - Taufiq Yuli Purnama; Mudji Rahardjo; Anik Tri Haryani; Retno Iswati (JURNAL DAYA-MAS, 2022)
Abstract— Village regulations are statutory regulations established by the Village Head after being discussed and agreed with the Village Consultative Body. Village regulations are needed to organize village government, limit power, and regulate village community life in order to achieve the goals of the State of Indonesia. The problem inthis journal is how community participation in the formation of regulations. Basically, every village has a different pattern of behavior and community habits in daily life, so there needs to be a concrete rule in the village itself, namely in the form of Village Regulations. Likewise with Keraswetan Village, Geneng District, NgawiRegency,it is necessary to have an understanding of the importance of community participation in the formation of village regulations. The method used in the implementation of this community service uses the legal counseling method. Based on the results of this study it was concluded that the importance of community participation in the formation of Village Regulations. Village regulations in principle are a village community decision that is used as the basis for implementing village government with the aim of regulating living together, protecting community rights and obligations, and maintaining community safety and order in administering village government in accordance with the wishes and aspirations of the community. The formation of Village Regulations must be in accordance with Law Number 12 of 2011 concerning the Formation of Legislation and the process of forming village regulations based on Law Number 6 of 2014 concerning Villages.